On Golden Pond [videorecording (DVD)] - Rydell, Mark, 1934-; Hepburn, Katharine, 1907-2003; Fonda, Henry, 1905-1982; Fonda, Jane, 1937-; McKeon, Doug, 1966-; Coleman, Dabney, 1932-; Garity, Troy (Artisan Home Entertainment, 2003)
Shows the conflicts between three generations as the Thayers, a crotchety old professor and his wife, spend their summer together on a lake in New England. The couple agrees to mind their estranged daughter's boyfriend's child, while daughter and boyfriend go on a trip. The boy bonds with the old man in a way his daughter never did. Shows the terrors and graces of aging.